Construction of Islam and the Muslims in the USA: Evidence from Print Media - Muhammad Tariq; Zafar Iqbal; Fazal Rahim Khan (Journal of Islamic Thought and Civilization, 2021)
The US media features a negative rhetoric against the Muslims by posing them as a threat to the West. This article/study aims to explore how the US media constructs the image of Islam and the Muslims for the viewers. It also aims to analyze the perspective of the US writers about Islam and the Muslims. The paper analyzes 2,523 articles, descriptive of Islam and the Muslims and published in the US press from January to March 2017. It explores and describes the level to which the negative words and metaphors are used in the leading articles, which eventually constructs a negative image of the Muslims and Islam among the US citizenry. This negative portrayal by the US media points to the emergence and evolution of the patterns of representation of Islam, which are constitutive of an existential threat image. The study recommends the analysis of all media actors who speak / write about Islam and the Muslims at a broader level to understand the problem in its true perspective/essence with an aim to explore its prognostics.